Blow-up criteria for the 2½D magnetic Bénard fluid system with partial viscosity. Issue 8 (10th June 2020) - Ma, Liangliang; Zhang, Lei
ABSTRACT: We study the Cauchy problem for the 2 1 2 D incompressible magnetic Bénard fluid system with partial viscosity and derive some blow-up criteria of smooth solutions. More precisely, we first obtain a blow-up criterion of smooth solutions to the 2 1 2 D magnetic Bénard fluid system without zero magnetic diffusion and thermal diffusivity. Furthermore, we derive two blow-up criteria of smooth solutions to the 2 1 2 D magnetic Bénard fluid system without dissipation.